2015
DOI: 10.1007/s11270-015-2513-4
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Methylene Blue from Aqueous Solution by the Activated Carbon Obtained from the Fruit of Catalpa bignonioides

Abstract: In this study, the fruit of Catalpa bignonioides was used as the raw material to obtain low-cost activated carbon. The activation process was carried out by using chemical activation method with zinc chloride. Catalpa activated carbon (CAC) was characterized using elemental analyzer, Brunauer-EmmetTeller (BET), scanning electron microscopy (SEM), Fourier transform infrared spectra (FTIR), and the point of zero charge (pH ZPC ). The BET surface area of CAC prepared by the impregnation ratio of 30 % ZnCl 2 (w/w)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…This might decelerates the adsorption speed of MB on to PDWAB with increase of MB concentrations especially high concentrations (C 0 = 75–150 mg/L) and thus the time for reaching the equilibrium of adsorption increases. Similar trends for the effects of contact time and initial dye concentration on adsorption of dyes were also found by other researchers .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This might decelerates the adsorption speed of MB on to PDWAB with increase of MB concentrations especially high concentrations (C 0 = 75–150 mg/L) and thus the time for reaching the equilibrium of adsorption increases. Similar trends for the effects of contact time and initial dye concentration on adsorption of dyes were also found by other researchers .…”
Section: Resultssupporting
confidence: 89%
“…At lower pH, the adsorbent surface functional groups (mainly oxygen‐containing groups) linked to the H + , making these groups inaccessible for positively charged dye molecule. With the increase of pH value, the deprotonation of functional groups provided the chance to coordinate with MB molecule, which is a cationic species . As shown previously, the pHzpc of PDWAB is 5.8.…”
Section: Resultsmentioning
confidence: 54%
“…e yield of the activated carbon prepared under the optimal conditions was 56.48%. e methylene blue adsorption capacity of the activated carbon obtained in this study is comparable to or greater than that of the activated carbons found in literature [38][39][40][41][42][43]. Figure 2 shows SEM micrographs of raw prickly pear seed cake and optimal activated carbon.…”
Section: Response Analysis and Interpretationsupporting
confidence: 75%
“…The reduction of AOX in the bleaching process has been realized by process optimization [14], the use of chemical additives [15,16] and pretreatment [11,[17][18][19]. Adsorption is the most widely used method in the treatment of organic pollutants [20][21][22]. This method has the advantages of a high removal efficiency, thorough purification, low energy consumption, mature technology and easy promotion [23].…”
Section: Introductionmentioning
confidence: 99%